Pengaruh Pengembangan Karir Terhadap Kinerja Karyawan Melalui Burnout Sebagai Variabel Mediasi Pada Karyawan Perusahaan Umum Daerah Air Minum Tirta Bumi Wibawa Kota Sukabumi - Restu Nurfani; Nor Norisanti; Resa Nurmala (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The success of an organization in maintaining its existence is through the development of human resources. PERUMDA Air Minum TBW Kota Sukabumi is a company engaged in the field of clean water services, the phenomenon faced by the company from the aspect of human resources is the low performance of employees indicated by the decline in employee punctuality to work hour regulations and employee attendance. The results of field observations on several employees showed the absence of career development, namely job rotation, with the absence of job rotation so far employees feel bored because they have been struggling in the same field for years. This study aims to determine the effect of career development on employee performance through burnout as a mediating variable. The research method used in this study is a quantitative method with a quasi-associative approach. The sampling technique used in this study is saturated sampling with a sample size of 52 employees. The data analysis technique used is Structural Equation Modeling Partial Least Square (SEM-PLS) with the help of SmartPls Version 3.2 software. The results of this study indicate that there is no significant influence between career development and employee performance, there is a significant influence between career development and burnout, and burnout cannot mediate career development and employee performance.